Physicochemical properties and stability of palm olein and rice bran oil blends / Nor Idayu Ismail - Ismail, Nor Idayu (2013)
The objectives of this study were to determine the changes in the physicochemical porperties of the oil after blending, to determine the stability of the oil blends and to identify the best mixing ratio for frying oil. Palm olein (POo) was blended with rice bran oil (RBO) at different ratios of 30:70, 50:50 and 70:30 POo:RBO. The physicochemical properties and stability of POo and RBO and their blends were determined based on the major fatty acids, cloud point (CP), smoke point (SP), iodine value (IV), free fatty acid (FFA), induction period (IP), viscosity and colour. Blending POo with RBO results in significant (p<0.05) increased of IV, SP and decrease in CP, FFA, IP and viscosity of all blends. Decreased in IP reduced the stability of oil blends. Blending also increased the oleic and linoleic acids but decreased the palmitic acid. Based on the results obtained, blend 30:70 POo:RBO was the most suitable blend for frying oil since this blend had the highest SP and lowest CP.